Analysis Of Misconceptions In Mathematical Problem Solving Integer Counting Operations Class IV Students Of SDN 3 Lape Sumbawa - Suryani, Suryani; Ramdhani, Lisda; Nurwalidainismawati, Nurwalidainismawati (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research aims to describe and analyze students' misconceptions in mathematics subjects, material for counting whole number operations, Class IV SDN 3 Lape Sumbawa. The type of research used is descriptive qualitative research. The research was conducted in class IV of SDN 3 Lape Sumbawa with a population of 25 students. The subjects consisted of 2 students randomly sumpling. The instruments used in this research were test questions, interview guidelines and also wide range of observations. The data analysis techniques in this research are as follows: 1) data reduction; 2) data presentation; and 3) withdrawal. The results of the research are that students' misconceptions are different in each question number. In Figure 1 there are misconceptions in grouping and performing arithmetic operations on multiplication. In Figure 2 there is an error in the concept of calculating addition and subtraction. In Figure 3, students have misconceptions about the concept of mixed multiplication calculation operations which are operated with repetition calculation operations. In Figure 4, students' misconceptions regarding multiplication calculation operations are students' misconceptions regarding the operation of multiplication and subtraction calculation operations. Misconceptions occur due to two factors; 1) The first factor is because students interpret new experiences or concepts, 2) The second is because of the emotional and intellectual feelings that have been attached to students, so students find it difficult to accept new concepts that are different from students' understanding.